Is the level of sustainability reporting an indicator of future value of a company? - Crowley, Michelle (My University, 2016)
The mode of reporting performance by firms has shifted radically in recent years from a set of audited annual financial statements, to the inclusion of integrated and sustainability reports. This move has been particularly important for South African listed firms, which are required to prepare integrated reports (and therefore sustainability reports) due to the revision of the Johannesburg Stock Exchange (JSE) listing requirements. Although there are no specific accounting standards at present particularly for sustainability reports, certain reporting frameworks, such as the Global Reporting Initiative (GRI) guidelines, have influenced and become leaders in such reporting. The value relevance of the quality of sustainability reports is the focus of this study. This research report tests whether report quality as measured by the GRI reporting categories is value relevant for JSE listed companies, whether better reporting companies achieve better long term performance over the period 2007 to 2015. Value relevance is measured using a 4 tiered portfolio construction technique, which uses the GRI reporting categories to define comparative investment portfolios. The results indicate that GRI firms with the highest report qualities underperformed significantly when compared to the market, with the exception of the C report firms, which showed some level of outperformance in the later portfolio years. Interestingly, the portfolio of firms using frameworks other than the GRI outperformed all of the categories of GRI framework firms, as well as the market. The results for the GRI category firms therefore contradict some of the previous research on the value relevance of sustainability reporting which used different measurement proxies for quality, while the non GRI reporting firm results find similar conclusions. This research report therefore concludes that the GRI framework implementation is relatively low in a South African context, and that the GRI report categories do not provide a measure of report quality for the purpose of measuring value relevance, and rather measure the breadth of reporting. This is partly due to the early stage of development of sustainability reporting within South Africa, as well as the lack of a mandatory assured reporting framework such as the GRI, resulting in many firms preferring not to use the globally favoured GRI framework. It appears that most firms are tailoring the various frameworks available to their needs rather than using a consistent framework, which results in reports not being based on the same framework, and therefore not being comparable, even on a high level indicator basis. This highlights the need for revisions to be introduced in the King IV report which will hopefully assist in formalising the leading sustainability framework, and therefore standardising sustainability reporting, together with providing a linkage to the Code for Responsible Investing in South Africa, which requires investors to integrate their investment decisions with sustainability considerations.
Thesis (M.Com. (Accountancy))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Accounting, 2016.
Keywords: Corporation reports--South Africa; Corporations--Accounting; Corporate governance--South Africa; Disclosure in accounting--South Africa; Social responsibility of business--South Africa